Analysis of Physical Activity in Atoni Meto Traditional Sports on North Central Timor Regency - Talan, Rudobertus; Nay, Florianus Aloysius; Andiwatir, Alexius (Jp.jok (Jurnal Pendidikan Jasmani, Olahraga dan Kesehatan), 2022)
The purpose of the study was to determine the physical activity and traditional sports of Atoni Meto in North Central Timor Regency. The initial stage of the research method is that researchers develop research instruments that will be used to explore information from sources in depth through direct observation (observation), in-depth interviews, focus grup discussion, and documentation studies to find physical activities and traditional sports Atoni Meto "Mantika" in North Central Timor Regency. In the data analysis process, the research team was based on the Miles and Huberman analysis model: data collection, data reduction, data presentation, and conclusion drawing (verification). The results showed that the physical components contained in the traditional Atoni Meto sport in North Central Timor Regency were the values of sportsmanship, endurance, strength, coordination, balance, and accuracy. Some of these sports components can be integrated into the learning process of Physical Education in Sports and Health at the elementary, middle, and high school levels.